Application of cinchona-sulfonate-based chiral zwitterionic ion exchangers for the separation of proline-containing dipeptide rotamers and determination of on-column isomerization parameters from dynamic elution profiles - Wernisch, Stefanie; Trapp, Oliver; Lindner, Wolfgang (Analytica chimica acta, 2013)
The interconversion of cis and trans isomers of dipeptides containing C-terminal proline was studied by dynamic chromatography on zwitterionic chiral stationary phases at temperatures ranging from −15°C to +45°C The cis-trans isomers could be separated below 0°C and above 0-10°C plateau formation and peak coalescence phenomena occurred, which is characteristic for a dynamic process at the time-scale of partitioning. At and above room temperature, full coalescence was observed, which allowed separations of enantiomers without interference from interconversion effects. Analysis of the dynamic elution profiles of the interconverting peptides allowed the determination of isomerization rate constants and thermodynamic activation parameters (isomerization enthalpy, entropy and activation energy). In accordance with established results, isomerization rates and thermodynamic parameters were found to depend on the nature of the N-terminal amino acid. Isomerization barriers were only slightly lower than values determined with other methods but significant differences in the relative contributions of the activation enthalpy and entropy as well as isomerization rates pointed toward selector-moderated isomerization dynamics.